2012 9th IEEE International Symposium on Biomedical Imaging (ISBI) 2012
DOI: 10.1109/isbi.2012.6235587
|View full text |Cite
|
Sign up to set email alerts
|

Emphysema quantification in a multi-scanner HRCT cohort using local intensity distributions

Abstract: This article investigates the suitability of local intensity distributions to analyze six emphysema classes in 342 CT scans obtained from 16 sites hosting scanners by 3 vendors and a total of 9 specific models in subjects with Chronic Obstructive Pulmonary Disease (COPD). We propose using kernel density estimation to deal with the inherent sparsity of local intensity histograms obtained from scarcely populated regions of interest. We validate our approach by leave-onesubject-out classification experiments and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 13 publications
(14 reference statements)
0
59
1
Order By: Relevance
“…This more parsimonious technique allows for a high degree of computational efficiency and scalability to large data sets. It has been previously shown that local lung density is the most discriminative feature in terms of classification performance when compared with local binary patterns with and without local density information (30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This more parsimonious technique allows for a high degree of computational efficiency and scalability to large data sets. It has been previously shown that local lung density is the most discriminative feature in terms of classification performance when compared with local binary patterns with and without local density information (30).…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of the emphysema pattern was performed using local histogram information (30). To train the algorithm, 267 CT scans at full inspiration from the COPDGene cohort were processed to yield 1,337 regions of interest (ROIs) of size 24.18 3 24.18 mm 2 .…”
Section: Local Histogram-based Quantitative Emphysema Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional quantitative CT analysis included classification of emphysema pattern based on local histogram information; the method for generating local histogram-based quantitative emphysema patterns in the COPDGene Study has been previously defined (30,31). On the basis of a set of expert-defined training images, an algorithm was developed to classify each lung region into one of six categories according to emphysema pattern: normal; mild, moderate, or severe centrilobular emphysema; panlobular emphysema; or pleural-based emphysema.…”
Section: Chest Ct Imagingmentioning
confidence: 99%
“…Pleural-based emphysema was defined as emphysema that abutted the chest wall. For each CT scan, the six categories of local histogram emphysema pattern are expressed as a fraction of total lung volume represented by each category of emphysema (30).…”
Section: Chest Ct Imagingmentioning
confidence: 99%